At the eye of the pandemic hurricane: What have we learned about the control of the public administration in Brazil? - Rhein Schirato, Vitor (2021)
The scope of this essay is to analyze some decisions of the Brazilian federal administration concerning actions to minimize the current pandemic of COVID-19 to understand to which extent such discretionary decisions could be subject to a judicial review. KEYWORDS: public administration, law, legal rule, judicial review of the administration, administrative court. JEL CODE: K0, K00, K23